OPTIMIZING INNOVATIVE PERFORMANCE THROUGH ETHICAL LEADERSHIP, TECHNOLOGICAL INNOVATION, AND ATTITUDES TOWARD PERFORMING WELL - Dafira Nadaa Septiani; Fatmah Bagis; Naelati Tubastuvi; Meydy Fauziridwan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Innovation in the healthcare sector requires hospitals to integrate ethical leadership and modern technology to improve service quality. This study aims to analyze the influence of ethical leadership and technological innovation on the innovative performance of hospital employees in Banjarnegara, and examine the role of attitudes toward good performance as a mediating variable. Innovative performance in this study is understood as the ability of employees to generate, communicate, and implement new ideas that are useful for improving work effectiveness and the quality of hospital services. Using quantitative methods with 342 respondents and PLS-SEM analysis, the study found that ethical leadership significantly influences innovative performance and attitudes toward performing well. Technological innovation does not directly influence innovative performance, but has a significant influence on attitudes toward performing well. In addition, attitudes toward performing well are proven to be the most powerful factor in driving innovative performance. This variable also mediates the relationship between ethical leadership and innovative performance, as well as the relationship between technological innovation and innovative performance. These findings indicate that innovation in healthcare does not solely depend on technology or policies, but on positive employee attitudes formed through ethical leadership and effective technological support. This study provides a practical contribution to hospital management in building an innovative work culture and improving the quality of healthcare services.